Priming of CD8+ T Cell Responses to Liver Stage Malaria Parasite Antigens - Corradin, Giampietro; Levitskaya, Jelena (Frontiers in Immunology, 2014)
While the role of malaria parasite-specific memory CD8+ T cells in the control of exo-erythrocytic stages of malaria infection is well documented and generally accepted, a debate is still ongoing regarding both the identity of the anatomic site where the activation of naive pathogen-specific T cells is taking place and contribution of different antigen presenting cells (APCs) into this process. Whereas some studies infer a role of professional APCs present in the lymph nodes draining the site of parasite injection by the mosquito, others argue in favor of the liver as a primary organ and hepatocytes as stimulators of naïve parasite-specific T cell responses. This review aims to critically analyze the current knowledge and outline new lines of research necessary to understand the induction of protective cellular immunity against the malaria parasite.